2016
DOI: 10.1093/ofid/ofw243
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Invasive Group A Streptococcal Infections in Remote Indigenous Communities in Northwestern Ontario, Canada

Abstract: Background.Worldwide, indigenous populations appear to be at increased risk for invasive group A streptococcal (iGAS) infections. Although there is empirical evidence that the burden of iGAS disease is significant among remote First Nations communities in Northwestern Ontario, Canada, the epidemiology of iGAS infections in the area remains poorly characterized.Methods.Individuals that met case definition for iGAS disease and whose laboratory specimens were processed by Meno Ya Win Health Centre in Sioux Lookou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 29 publications
(30 reference statements)
2
30
0
Order By: Relevance
“…A recent epidemiological study on iGAS strains from remote indigenous communities in Northwestern Ontario, over the period 2009–2014, indicated that among 46 invasive isolates, 14 different emm types were identified, with emm -type variability observed over time. The most common emm types were emm 114 (17.4%), emm 11 (15.2%), emm 118 (13.0%), emm 68, and emm 82 (10.9% each) ( 62 ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent epidemiological study on iGAS strains from remote indigenous communities in Northwestern Ontario, over the period 2009–2014, indicated that among 46 invasive isolates, 14 different emm types were identified, with emm -type variability observed over time. The most common emm types were emm 114 (17.4%), emm 11 (15.2%), emm 118 (13.0%), emm 68, and emm 82 (10.9% each) ( 62 ).…”
Section: Resultsmentioning
confidence: 99%
“…An important social wakeup since the 2003 SARS pandemic is the emergence of the Truth and Reconciliation process in Canada, recognizing the historical cultural genocide of Indigenous peoples caused in part by abuses in government-supported residential schools (Smylie and Firestone 2016). Indigenous peoples in Canada have faced myriad of social, environmental, and biological disasters including the ongoing suicide crisis (Webster 2016), access to safe drinking water (Bradford et al 2016) and infectious diseases including group A streptococcal (iGAS) infections, rheumatic fever (Bocking et al 2016), tuberculosis (Patel et al 2017), and the 2009 pH1N1 (Jung et al 2017). The sustained high incidence of infectious disease in Indigenous peoples coupled with decreasing incidence in the rest of the Canadian population is suggested to be caused by 'structural violence' such that social structures, institutions, culture, and other factors combine to inform these extreme health disparities (Galtung 1969).…”
Section: Evolving Societies-where To From Here?mentioning
confidence: 99%
“…Similarly, China itself reported similar discrimination on a national level against those from Wuhan, the epicentre of the outbreak (Ren et al, 2020). Work on indigenous communities has also linked ethnicity and associated structural violence issues to health inequalities, with research pointing to higher rates of infection for diseases such as HIV (Negin et al, 2015), tuberculosis (Romero-Sandoval et al, 2007;Tuite et al, 2017), malaria (Donnelly et al, 2016) and streptococcal Infections (Bocking et al, 2017). For communities that not only suffer stigma, but also live in poor socioeconomic conditions, or in remote communities (the protective effect of which will likely depend on long-distance social connections), access to medical aid and information in the context of COVID-19 may be problematic.…”
Section: Intersections Of Vulnerability In Times Of Coronavirusmentioning
confidence: 98%